2020
DOI: 10.1021/acsomega.9b03786
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Comparison of the Combustion Behavior for Low-Temperature Combustion of n-Nonane

Abstract: To meet the increasing need for clean combustion, improve the combustion efficiency of fuels, and reduce the pollutants produced in the combustion process, it is necessary to systematically study the combustion of hydrocarbon fuels. An accurate and detailed chemical kinetic model is an important prerequisite for understanding the combustion performance of hydrocarbon fuels and studying complex chemical reaction networks. Therefore, based on ReaxGen, new detailed mechanisms for the lowtemperature combustion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…In Figure 1 b,c, after the upper end of the flame reached the surface of the porous media, the lower end of the flame still developed laterally but did not pass through the porous medium and eventually the flame was quenched. 17 That is to say, the flame was quenched in the porous media.…”
Section: Resultsmentioning
confidence: 99%
“…In Figure 1 b,c, after the upper end of the flame reached the surface of the porous media, the lower end of the flame still developed laterally but did not pass through the porous medium and eventually the flame was quenched. 17 That is to say, the flame was quenched in the porous media.…”
Section: Resultsmentioning
confidence: 99%
“…The initial calculated pressure is ranged from 3.5 to 3.2 × 10 7 Pa, which covers the working range of the common combustion devices, and the explosion temperature searching range is 350–2500 K. Other criteria like an average pressure increase rate of 3%/ms can be found for the determination of the cool flame ignition. 21 …”
Section: Numerical Approach Methodsmentioning
confidence: 99%
“…The initial calculated pressure is ranged from 3.5 to 3.2 × 10 7 Pa, which covers the working range of the common combustion devices, and the explosion temperature searching range is 350−2500 K. Other criteria like an average pressure increase rate of 3%/ms can be found for the determination of the cool flame ignition. 21 Three different detailed chemical kinetic models are used in this study, which are the comprehensive iso-octane combustion model (KAUST), 22 Aramco 2.0 model, 23 and methane/ propane oxidation model 24 from the National University of Ireland Galway (NUIG). As the KAUST and Aramco 2.0 models include larger hydrocarbon molecules, only the C3 subset species and related reactions are used in this study.…”
Section: Numerical Approach Methodsmentioning
confidence: 99%
“…Another criterion like an average pressure rise rate of 3%/ms was used for the determination of cool flame ignition. 33 The explosion limit is the temperature vs pressure boundaries between the explosion and nonexplosion conditions.…”
Section: Methodsmentioning
confidence: 99%
“…The first is that they exhibit negative temperature coefficients of the reaction rate. 1 Newitt and Thornes found that the spontaneous ignition temperature of the propane–oxygen mixtures showed a negative temperature coefficient (NTC) behavior. 2 A characteristic negative coefficient behavior was also observed when the ignition delay times for the propane/air mixtures were plotted as a function of temperature.…”
Section: Introductionmentioning
confidence: 99%